New ombudsman newspaper El Colombiano,critical study of his discourse - Pardo Abril, Neyla Graciela; Ospina Raigosa, Luis Eduardo (Folios, revista de la Facultad de Comunicaciones y Filología, 2014)
Over the past 10 years, the Newspaper El Colombiano has exhibited a political trend which has put forward criticism by several social sectors. This article carries out a discourse analysis on this newspaper ́s Press Ombudsman so as to determine the way it responds to such a questioning. Wondering about the communicative purposes that the Press Ombudsman has is rather relevant in order to understand its role within such a newspaper.This Critical Discourse Study (CDS) concludes that Press Ombudsman is a mechanism used by El Colombiano to Project a trust image on its contents, reinforced on every column. Its purpose is not guaranteeing quality of information. It is rather the public space which helps to construct and identity bond with the reader so as to strengthen the newspaper ́s positive image as well as its information ground. Researh of this critical natureprovides colombian journalism with reflections from a critical and self-critical perspective, which is not widespread in this field.